Rituximab resistance in ITP and beyond - Xiao, Zhengrui; Murakhovskaya, Irina (Frontiers in Immunology, 2023)
The pathophysiology of immune thrombocytopenia (ITP) is complex and encompasses innate and adaptive immune responses, as well as megakaryocyte dysfunction. Rituximab is administered in relapsed cases and has the added benefit of inducing treatment-free remission in over 50% of patients. Nevertheless, the responses to this therapy are not long-lasting, and resistance development is frequent. B cells, T cells, and plasma cells play a role in developing resistance. To overcome this resistance, targeting these pathways through splenectomy and novel therapies that target FcγR pathway, FcRn, complement, B cells, plasma cells, and T cells can be useful. This review will summarize the pathogenesis mechanisms implicated in rituximab resistance and examine the potential therapeutic interventions to overcome it. This review will explore the efficacy of established therapies, as well as novel therapeutic approaches and agents currently in development.